2020
DOI: 10.1080/14786419.2020.1837815
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera (Lam.): a natural remedy for ageing?

Abstract: disorderss. Effect of Moringa oleifera, is an age old ingredient of Indian aurvedic and traditional medicine was tested for its effect on age related antioxidant activity in Wistar albino rats of three age groups (6 and 18 months old) Aqueous extract of. M. oleifera leaves (MOAE) was administered orally at a dosage of 200mg/kg body wt. for a period of 30 days. MOAE treatment showed significant reduction in lipid peroxidation and lipofuscin pigmentation along with elevated serotonin and antioxidant enzymes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Particularly, these polyphenols presented in moringa have been detected and quantified in blood (quercetin at a concentration of 0.0723 ± 0.0810 µM; kaempferol at a concentration of 0.0579 ± 0.0609 µM; apigenin at a concentration of 0.0106 ± 0.0123 µM and gallic acid at a concentration of 0.007 ± 0.003 µM) [ 52 , 53 , 54 ]. Additionally, Nair et al (2020) have recently demonstrated that compounds presented in moringa extracts are able to pass across Blood-brain-barrier (BBB) and to reach its pharmacological target [ 55 ]. Regarding the safe toxicological profile of moringa, doses of up to 2000 mg/kg of methanol and aqueous leaf extract were safe in animal studies [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, these polyphenols presented in moringa have been detected and quantified in blood (quercetin at a concentration of 0.0723 ± 0.0810 µM; kaempferol at a concentration of 0.0579 ± 0.0609 µM; apigenin at a concentration of 0.0106 ± 0.0123 µM and gallic acid at a concentration of 0.007 ± 0.003 µM) [ 52 , 53 , 54 ]. Additionally, Nair et al (2020) have recently demonstrated that compounds presented in moringa extracts are able to pass across Blood-brain-barrier (BBB) and to reach its pharmacological target [ 55 ]. Regarding the safe toxicological profile of moringa, doses of up to 2000 mg/kg of methanol and aqueous leaf extract were safe in animal studies [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, M. oleifera leaf extracts displayed anti-aging activity by improving oxidative stress resistance and nutrient-sensing pathways ( 10 ), extending the life span, and improving stress tolerance of Caenorhabditis elegans ( 11 ). Moreover, it was also found that the M. oleifera leaf extracts observably decreased age-related neurodegeneration in the old treated rat model ( 12 ), and its cream restored skin vitality and reduced skin aging ( 13 ). However, the specific bioactive ingredients in M. oleifera leaf extracts that contributed most to its conspicuous antiaging activity remain unexplored until now.…”
Section: Introductionmentioning
confidence: 96%
“…The anti-aging effects of Moringa oleifera seem not to be limited to the skin. In a rat model, oral administration of an aqueous extract of M. oleifera leaves (200 mg/kg) for 30 days determined significant reductions in lipid peroxidation and lipofuscin pigmentation along with elevated serotonin and antioxidant enzymes in the brain tissue [55]. Other studies confirmed that Moringa alleviates stress and has a neuroprotective function in murine models [56].…”
Section: Discussionmentioning
confidence: 87%